KINETIC ANALYSIS OF PHOSPHATE ADSORPTION ON ZEOLITE AND ACTIVATED CARBON IN GREYWATER - Devy Cendekia; Dian Ayu Afifah; Yeni Variyana; Evita Karlina (Fakultas Teknik Universitas Wahid Hasyim, 2024)
Phosphate is one of the pollutants that exist in greywater. Phosphate pollutant comes from surfactants used in detergent products which are commonly used in household activities. Water phosphate will increase when detergent waste is not managed properly. The presence of phosphate in waters can result in eutrophication which disrupts aquatic life. Some natural adsorbents such as zeolite and activated carbon can adsorb phosphate in greywater. The effectiveness of an adsorbent in removing phosphate in greywater can be analyzed based on the adsorption capacity and adsorption rate. In this research, it is known that zeolite is more effective as an adsorbent in removing phosphate content in greywater. Zeolite and activated carbon follow the Freundilch adsorption mechanism in the adsorption of phosphate in water. Zeolite can adsorb 41.154% with a contact time of 40 minutes, with a Freundilch constant (Kf ) = 8.10 L g-1 and an adsorption rate of K = 0.0038 m-1. For activated carbon it can adsorb 23.330 % with a contact time of 40 minutes, with a Freundilch constant (Kf ) = 1.99 L g-1 and an adsorption rate of K = 0.0013 m-1. Based on these data, activated carbon has a faster phosphate adsorption rate than zeolite, but has a smaller adsorption capacity value than zeolite. So that the zeolite can absorb more phosphate in greywater, with an adsorption rate of 0.0038 per minute.